Pengembangan metode penilaian ganti rugi usaha pariwisata bahari akibat insiden pencemaran minyak di laut - Gatot Yulianto; Ali Mashar; Sugeng Hari Wisudo; Luluk Dwi Wulan Handayani; Irza Arnita nur; Hadi Supardi; Audra Nur; Luisa Febrina Amalo; Marfian Dwidima Putra; Yusli wardiatno; Hefni Effendi (Graduate School Bogor Agricultural University (SPs IPB), 2021)
One of the functions of the coastal ecosystem is to produce environmental services that can be used for marine tourism. Oil pollution incidents at the sea have caused a decline in the quality of marine tourism objects, thus reducing the number of visitors arriving and then it has implications for decreasing the income of the people who do business at tourist area. The community's claim for immediate compensation payments requires a faster calculation method. The purpose of this research is to develop a method of assessing the economic compensation for marine tourism businesses that are affected by incidents of oil pollution at the sea. The type of this research is descriptive research. The data consists of primary data and secondary data. The steps required in calculating compensation are (1) identifying tourism businesses, (2) building a theoretical concept of compensation, (3) determining the legal basis for calculating compensation, and (4) Designing a compensation formula. The application of the five compensation calculation formulas requires 18 variables. By taking the case of an oil spill incident in the North Sea of ​​Karawang which has an impact on Tanjung Pakis beach tourism, an estimate of the value of compensation (Rp/day) is obtained for the buoy rental service business is Rp 111,323.08, for bathroom services business is Rp 69,504.62, for food/beverage trading business on a small scale is Rp 71,510.77 and for food/beverage trading business on a large scale is Rp 188,569.23. For the next stage, the implementation of compensation needs to be verified against the impacted community and the payment mechanism so that it is right on target.